2009
DOI: 10.1165/rcmb.2008-0367oc
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 1 Contributes to ATP Release in Airway Epithelia

Abstract: ATP is a paracrine regulator of critical airway epithelial cell functions, but the mechanism of its release is poorly understood. Pannexin (Panx) proteins, related to invertebrate innexins, form channels (called pannexons) that are able to release ATP from several cell types. Thus, ATP release via pannexons was examined in airway epithelial cells. Quantitative RT-PCR showed Panx1 expression in normal human airway epithelial cells during redifferentiation at the air-liquid interface (ALI), at a level comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
253
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(268 citation statements)
references
References 61 publications
11
253
3
1
Order By: Relevance
“…Furthermore, ATP release or surrogate measures are correlated with Panx1 expression levels. In knockdown experiments with Panx1 siRNA/shRNA, the ATP release is largely attenuated [3,14]. Also, the pharmacology of Panx1 channels matches that of ATP release.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Furthermore, ATP release or surrogate measures are correlated with Panx1 expression levels. In knockdown experiments with Panx1 siRNA/shRNA, the ATP release is largely attenuated [3,14]. Also, the pharmacology of Panx1 channels matches that of ATP release.…”
Section: Introductionmentioning
confidence: 74%
“…However, instead of forming the intercellular channels of gap junctions as connexins do, pannexins operate as unpaired pannexons, allowing the flux of molecules from the cytoplasm to the extracellular space and vice versa [1]. It has been recognized that Pannexin1 (Panx1) exerts a key role in the release of ATP [2][3][4][5]. In this function Panx1 contributes to the propagation of intercellular calcium waves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence for ATP release through ATPbinding cassette (ABC) transporters, connexin hemichannels and multiple Cl − channels [12][13][14]. More recent studies have found that pannexin1 hemichannels play a key role in ATP release from many different cells [15][16][17][18]. Vesicular exocytosis may also contribute to ATP release [19][20][21].…”
Section: Introductionmentioning
confidence: 99%